Pengaruh Literasi Keuangan, Kemudahan Penggunaan, dan Risiko Penggunaan terhadap Keputusan Penggunaan Dompet Digital DANA pada Pekerja di DKI Jakarta - Rayhannevi Rayhannevi; Saparuddin Mukhtar; Herlitah Herlitah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of financial literacy, perceived ease of use, and perceived risk on the usage decision of the digital wallet DANA among workers in DKI Jakarta. A quantitative approach with a causal research design was employed, involving 150 respondents selected using purposive sampling. Data were collected through online questionnaires and analyzed using IBM SPSS Statistics, including validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing. The findings indicate that financial literacy, perceived ease of use, and perceived risk have a positive and significant effect on usage decision, both partially and simultaneously. Financial literacy was identified as the most dominant variable influencing usage decision, followed by perceived ease of use and perceived risk. The coefficient of determination (R²) showed that the three independent variables jointly explained 67.1% of the variation in usage decision, while the remaining 32.9% were explained by other factors outside the model, such as perceived usefulness, trust, or social influence. These findings support the Human Capital Theory and the Technology Acceptance Model (TAM), suggesting that the decision to use DANA among workers in DKI Jakarta is driven not only by financial literacy but also by ease of use and manageable risk perception. This study contributes to the understanding of consumer behavior in the context of digital payment systems and provides practical insights for digital wallet providers and regulators in designing more effective strategies to encourage sustainable usage.